2021
DOI: 10.1029/2020jd033527
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Variation of Turbulent Entrainment Mixing Processes in Marine Stratocumulus Clouds Using High‐Resolution Digital Holography

Abstract: Marine stratocumulus clouds contribute significantly to the Earth's radiation budget due to their extensive coverage and high albedo. Yet, subgrid variability in cloud properties, such as aerosol concentration, droplet number, and precipitation rates, lead to considerable errors in global climate models. While these clouds usually have small vertical extent, turbulent entrainment‐mixing and precipitation can generate significant variations in droplet number, size, and relative dispersion with altitude. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…In this scenario, number concentration decreases but droplet size remains unchanged. Some observational studies support the extreme IM concept (Burnet and Brenguier, 2007;Lu et al, 2011;Freud et al, 2011Freud et al, , 2008Pawlowska et al, 2000;Haman et al, 2007), while some others indicate that the HM mixing dominates (Gerber et al, 2008;Lu et al, 2013c;Burnet and Brenguier, 2007;Jensen et al, 1985), and still some others find intermediate features fall in between the HM and IM mixing (Lehmann et al, 2009;Lu et al, 2014a;Kumar et al, 2018).…”
mentioning
confidence: 95%
“…In this scenario, number concentration decreases but droplet size remains unchanged. Some observational studies support the extreme IM concept (Burnet and Brenguier, 2007;Lu et al, 2011;Freud et al, 2011Freud et al, , 2008Pawlowska et al, 2000;Haman et al, 2007), while some others indicate that the HM mixing dominates (Gerber et al, 2008;Lu et al, 2013c;Burnet and Brenguier, 2007;Jensen et al, 1985), and still some others find intermediate features fall in between the HM and IM mixing (Lehmann et al, 2009;Lu et al, 2014a;Kumar et al, 2018).…”
mentioning
confidence: 95%
“…It is also worthwhile to briefly discuss why the cloud top evaporation rate is not directly impacted by the droplet concentration (as seen in Figure 4). Recent studies have found that at the tops of stratocumulus clouds the timescale for mixing is much larger than the timescale for evaporation leading to inhomogeneous mixing (Desai et al, 2021;Gao et al, 2021). This result suggests that the bulk evaporation rate at cloud top is controlled primarily by how fast dry air can be entrained into the cloud rather than by the microphysical properties of the cloud droplets.…”
Section: Discussionmentioning
confidence: 99%
“…The entrainment and mixing process on cloud edges can affect the in-cloud water through mass exchange [25][26][27]. It is noteworthy that the entrainment and mixing process remains poorly understood, and that its measurement and quantification are extremely difficult [28][29][30][31]. Thus, this study only focuses on the mechanisms unassociated with the surrounding ambiance.…”
Section: Introductionmentioning
confidence: 99%